Candidate genes for age at menarche are associated with endometriosis. Issue 5 (November 2020) - Ponomarenko, Irina; Reshetnikov, Evgeny; Polonikov, Alexey; Verzilina, Irina; Sorokina, Inna; Elgaeva, Elizaveta E; Tsepilov, Yakov A; Yermachenko, Anna; Dvornyk, Volodymyr; Churnosov, Mikhail
Abstract: Research question: Are the candidate genes for age at menarche associated with a risk of endometriosis? Design: Fifty-two candidate single nucleotide polymorphisms (SNP) for age at menarche, their gene–gene and gene–environment interactions were analysed for possible association with endometriosis in a sample of 395 patients and 981 controls. Association of the polymorphisms was analysed using logistic regression according to three main genetic models (additive, recessive and dominant). The gene–gene and gene–environment interactions were analysed for the second-, third- and fourth-order models with adjustment for covariates and multiple comparisons with subsequent cross-validation. Results: Sixteen SNP for age at menarche out of the 52 studied were associated with endometriosis. Polymorphism rs6589964 BSX was associated with endometriosis according to the additive and recessive models (OR 1.27–1.47, P perm ≤ 0.006). Fourteen SNP were associated with the disease within 12 most significant models of gene–gene interactions ( P perm ≤ 0.008). Twelve SNP involved in 10 most significant models of SNP–induced abortion interactions are associated with endometriosis. Fourteen of the 16 polymorphisms associated with endometriosis demonstrated pleiotropic effects: they were also associated with either age at menarche (7 SNP) or height and/or body mass index (10 SNP) in the studied sample. The 16 SNP associated with endometriosis and 316 SNP linked to them have regulatory and expression quantitative trait locus significance for 28 genes contributing to the G alpha signal pathway (fold enrichment 31.09, P FDR = 0.001) and responses to endogenous stimuli (fold enrichment 16.01, P FDR = 0.027). Conclusions: Sixteen SNP for age at menarche out of the 52 studied were associated with endometriosis.